Evaluation of a Short-form Functional Capacity Evaluation: Less may be Best - Gross, Douglas P.; Battié, Michele C.; Asante, Alexander K. (Journal of occupational rehabilitation, 2007)
Functional Capacity Evaluation (FCE) contributes to clinical decisions regarding fitness-for-work and may improve return-to-work outcomes. However, FCE is a burdensome clinical tool in terms of time and cost. We evaluated the effectiveness of a short-form FCE protocol. A cluster randomized controlled trial was conducted. Data were collected on all claimants undergoing FCE at Alberta's workers' compensation rehabilitation facility. Twenty-three clinicians who were trained and experienced with FCE were randomized to either an intervention or control group. The intervention group was trained to conduct short-form FCE and used this protocol through the trial's duration, while the control group continued standard FCE procedures. Data on subject characteristics, administrative outcomes (days to suspension of time loss benefits, days to claim closure, and future recurrence) and claimant satisfaction were extracted from the WCB-Alberta computer databases. Clinicians logged time taken to complete assessments. Analysis included examining differences between groups using independent samples t tests, Cox and logistic regression. Subjects included 372 claimants of whom 173 were tested with short-form FCE. Subjects were predominantly employed (64%) males (69%) with chronic musculoskeletal conditions (median duration 252 days). Administrative recovery outcomes were similar between groups as were claimant satisfaction ratings. No statistically significant or clinically relevant differences were observed on these outcomes between groups. A 43% reduction in functional assessment time was seen. A short-form FCE appears to reduce time of assessment while not affecting recovery outcomes when compared to standard FCE administration. Such a protocol may be an efficient option for therapists performing fitness-for-work assessments.